(NsOBRANIE SO^INENIJ W DWENADCATI TOMAH(B; s (NbESY(B: [(NrOMAN(B] / s (N~ASTX (B8s - (NdOSTOEWSKIJ(B, (NfEDORs ((NmOSKWA(B: s (NpRAWDA(B, s, 1982)
(Nw WOSXMOJ TOM WO[LI PERWYE DWE ^ASTI ROMANA (B"(NbESY(B".s
rus
Keywords: (NsATIRI^ESKIJ ROMANs; (NpSIHOLOGI^ESKIJ ROMANs